Current Status and Vulnerability Induced by Saline Intrusion in The Climate Change Context in Da Nang City - Truc, Nguyen Ngoc; Thinh, Truong Van; Thuong, Nguyen Van; Ly, Nguyen Thao (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Climate change and sea level rise are exacerbating saline intrusion in the coastal plains. Saline intrusion affects the infrastructure, the economy, society, and local livelihoods. Based on the method of the IPCC-UNESCO IHE, this study focused on the vulnerability assessment induced by saline intrusion at the level of wards and communes in Da Nang. It was carried out through three components, i.e. exposure, sensitivity, and adaptive capacity, with five factors, i.e. economy, society, natural conditions - environment - ecology, infrastructure, and urban governance. The obtained results showed that the highest vulnerability to saline intrusion in Da Nang city is in Hoa Quy and Hoa Xuan communes; 11 wards and communes were classified as highly vulnerable; 21 communes and communes have average vulnerability; 22 wards and communes are classified as low vulnerability. Keywords Saline intrusion, sea level rise, vulnerability assessment, adaptive capacity, Da Nang References [1] Bộ Tài nguyên và Môi trường, 2012. Kịch bản biến đổi khí hậu và nước biển dâng cho Việt Nam. Nhà xuất bản Tài nguyên - Môi trường và Bản đồ Việt Nam. [2] Bộ Tài nguyên và Môi trường, 2016. Kịch bản biến đổi khí hậu và nước biển dâng cho Việt Nam. Nhà xuất bản Tài nguyên - Môi trường và Bản đồ Việt Nam. [3] Nguyễn Văn Thắng và nnk, 2010. Biến đổi khí hậu và tác động ở Việt Nam. Nhà Xuất bản Khoa họcvà Kỹ thuật, Trang 196-200. [4] National Oceanic and Atmospheric Administration (NOAA), 1999. Community vulnerability assessment tool: New Hanover county, North Carolina case study, Washington D.C. [5] Cutter S. L., 1996. Vulnerability to environmental hazards”, Progress in Human Geography 20, p.529. [6] Cutter S. L., Mitchell J. T., Scott M. S., 2000. Revealing the vulnerability of people and places: a case study of Georgetown county, South Carolina. Annals of the Association of American Geographers, 90 (4),p.713. [7] IPCC, 2007. IPCC fourth assessment report. The AR4 synthesis report, Glossary. [8] www.unesco-ihe-fvi.org [9] Tổng cục Thống kê, 2012. Niên giám thống kê quận Liên Chiểu năm 2012, NXB Thống kê. [10] Tổng cục Thống kê, 2012. Niên giám thống kê quận Cẩm Lệ năm 2012. Nhà Xuất bản Thống kê. [11] Tổng cục Thống kê, 2012. Niên giám thống kê huyện Hòa Vang năm 2011 và 2012. Nhà Xuất bản Thống kê.